Eco-Epidemiology and Treatment of Babesiosis in Cervids - Milnes, Ellie L. (University of Guelph, 2018)
Babesia odocoilei, a protozoan hemoparasite of white-tailed deer (Odocoileus virginianus) transmitted by Ixodes scapularis ticks, is an increasingly recognized cause of disease in cervids in North America. Following an outbreak of babesiosis in reindeer (Rangifer tarandus tarandus) and wapiti (Cervus canadensis) at the Toronto Zoo in Ontario, Canada, we utilized a prospective postmortem survey to investigate the prevalence of B. odocoilei in wild, farmed, and zoo cervids in Ontario (n=270; 2016-2018) by polymerase chain reaction (PCR) and sequencing of spleen sample extracts. Babesia odocoilei was identified in 1.4% (2/142) of farmed red deer (Cervus elaphus), 4.4% (3/68) of wild white-tailed deer, and 3.4% (1/29) of captive wapiti. Wild white-tailed deer are the candidate wildlife reservoir for B. odocoilei in Ontario. Additionally, we designed a study to investigate the hypothesis that birds can disperse B. odocoilei-infected ticks along migratory flyways. Birds (n = 1,102) were captured during spring migration; the prevalence of I. scapularis infestation was 3.2% in 2016 and 6.7% in 2017, and 0.2% of birds carried one or more I. scapularis ticks that tested PCR-positive for B. odocoilei. Blanket dragging for questing ticks in southern Ontario revealed a minimum infection prevalence for B. odocoilei of up to 4.1% in ticks found in environments used by wild cervids. Babesia odocoilei can cause acute hemolytic crisis in susceptible cervids, thus evidence-based drug treatment protocols are needed to manage the disease. A single intramuscular injection of the anti-protozoal drug imidocarb dipropionate at 3.0 mg/kg may be useful for treatment of cervid babesiosis. To investigate this claim, a pharmacokinetic study of imidocarb was performed in 10 white-tailed deer. Plasma concentrations of imidocarb were determined using high-performance liquid chromatography. The disposition of plasma imidocarb was best characterised by a two-compartment open model, with rapid distribution and slow elimination. The mean  SD ...